Weed species composition of maize fields in Germany is influenced by site and crop sequence. (22nd June 2015) - de Mol, F; von Redwitz, C; Gerowitt, B
Summary: During the last decade, maize has become the crop with the second largest acreage in Germany. Therefore, agricultural advisors and the plant protection sector are interested in an overview of the weed species composition in maize fields, their determining factors and trends. From 2001 to 2009, a weed survey was conducted in 1460 maize fields throughout Germany. Data on crop management and soil characteristics were collected via farmer questionnaires. Principal component analysis and redundancy analysis were used to analyse patterns in weed species composition. The late spring and summer germinating species Chenopodium spp., Echinochloa crus‐galli and Solanum nigrum occurred with high densities and frequencies, but their occurrence was determined by different factors. Other frequent weed species were those that typically accompany autumn‐sown crops. The variation in species composition was significantly related to environmental factors (9.1% explained variance), particularly geographical latitude and precipitation, and management factors (4.7% explained variance), particularly crop sequence. The relative importance of these factors seems universal, when compared with surveys in other crops and regions. The factor 'year' was of minor importance (0.9% explained variance). Over the 9‐year period, no changes in weed species composition could be determined. The results suggest that despite the limited impact of crop management on weed species composition, farmers can use crop sequence to suppress individual species. The survey furthermore sets a baseline against which future changes can be measured in a landscape of rapidly changing agricultural land use.